Unraveling the global landscape of Elizabethkingia antibiotic resistance: A systematic review and meta-analysis - Saade Abdalkareem Jasim; Jaafaru Sani Mohammed; Rangaswamy Roopashree; Mohammad Y. Alshahrani; Aanchal Sharma; Abhishek Sharma; Shodiyev Asliddin; Masoumeh Beig (PLoS ONE, 2025)
Background The emergence of antibiotic-resistant Elizabethkingia strains poses a significant challenge in clinical settings. This systematic review and meta-analysis provide a comprehensive assessment of the prevalence of antibiotic resistance among Elizabethkingia isolates across different regions worldwide. Methods A systematic literature search was conducted across PubMed, Embase, Web of Science, and Scopus from 1998 to January 9, 2024, using predefined search strategies. Eligible studies reporting antibiotic resistance in Elizabethkingia were included. A random-effects model was applied to estimate resistance proportions and assess heterogeneity. Additional analyses, including meta-regression, subgroup evaluations, and assessments of outliers and influential studies, were performed to explore resistance trends and evaluate publication bias. Study quality was assessed using the Joanna Briggs Institute Checklist, and all statistical analyses were conducted using R with the metafor package. Results A total of 1,016 articles were identified, of which 34 studies (47 reports) met the inclusion criteria. The pooled analysis indicated high resistance to ceftazidime (88.5% of isolates, 95% CI: 21.1%–99.5%) with no significant heterogeneity. Resistance to rifampin was 12.5% (95% CI: 5.9%–24.7%), showing substantial heterogeneity, while ciprofloxacin resistance was 27.9% (95% CI: 13.8%–48.4%) with considerable heterogeneity. Among specific antibiotics, cefotaxime resistance was 96.1% (220 isolates), meropenem resistance was 92.4% (353 isolates), and gentamicin resistance was 77.7% (356 isolates). Additionally, sulfamethoxazole resistance was 46.1% (176 out of 360 isolates, 95% CI: 23.5%–70.4%), displaying significant heterogeneity. Conclusion This study highlights the widespread antibiotic resistance in Elizabethkingia, underscoring the urgent need for targeted treatment strategies and enhanced surveillance programs. The findings emphasize the importance of monitoring local resistance patterns to guide clinical decision-making. Future research should focus on elucidating resistance mechanisms and genetic diversity to develop practical therapeutic approaches and mitigate the global health impact of Elizabethkingia infections.